Improving The Writing Ability At The Tenth Year Students Of SMKN 2 Parepare By Using Diary Writing Strategy - Turrahma, Aulia (La Parole : Journal of Language Teaching and Pedagogy, 2018)
The objective of this research was to find out whether or not the use of diary writing strategy was able to improve the Writing ability at The Tenth Year Students of SMK Negeri 2 Parepare. This research used a quasi-experimental method with two classes as sample. The researcher taught the students by Using Diary Writing Strategy. The population of this research was the tenth year students at SMK Negeri 2 Parepare in academic year 2017/2018. The sample of the research consisted of 26 students from two classes taken from the population by using cluster random sampling. The results of data analysis showed that students' writing ability improved. It was shown by the mean score of pre-test that is 50.27 and post-test 75.73. It showed that the writing ability at the tenth year students of SMK Negeri 2 Parepare improved by using diary writing strategy. After analyzing the data by using SPSS version 21, the result of the probability value on the post-test was 0.002 and the significance value was 0.05. The data indicated that H0was rejected and H1 was accepted. It means that the writing ability at the tenth year students of SMK Negeri 2 Parepare before and after treatment was significantly different. In conclusion, teaching writing by using diary writing strategy was effective to improve the writing ability of eleventh grade students of SMK Negeri 2 Parepare in academic year 2017/2018.